2019
DOI: 10.1186/s13643-019-1056-y
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine infectious diseases consultations and clinical outcomes: a systematic review and meta-analysis protocol

Abstract: Background Telemedicine use is increasing in many specialties, but its impact on clinical outcomes in infectious diseases has not been systematically studied and reviewed. The proposed systematic review will evaluate the current evidence regarding the effect of telemedicine infectious diseases consultation on a range of clinical outcomes, including mortality, hospital readmission, antimicrobial use, and cost. Method/design Standard systematic review methodology will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Inadequate existing bed capacity is an obvious reason for long waiting lists for elective procedures in NHS hospitals. The effects of switching to telemedicine for patient consultations has been discussed [28] and this may be a choice for patients with an infectious disease with early symptoms who could be managed at home. Using appropriate but narrow admission and discharge policies to streamline patient flow for patients who are more ill has been effective in some epidemics in resource constrained situations [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate existing bed capacity is an obvious reason for long waiting lists for elective procedures in NHS hospitals. The effects of switching to telemedicine for patient consultations has been discussed [28] and this may be a choice for patients with an infectious disease with early symptoms who could be managed at home. Using appropriate but narrow admission and discharge policies to streamline patient flow for patients who are more ill has been effective in some epidemics in resource constrained situations [29].…”
Section: Discussionmentioning
confidence: 99%
“…While face-to-face consultation is commonplace in the US and may be preferable, it is not always readily available in all circumstances and resource-limited settings. In these situations, it may be especially important to implement other pathways and stewardship interventions to optimize care [42,43,122,123]. A recent study evaluated published data on outcomes of telemedicine vs in-person ID consultation, but the variety of methods and outcomes used in the primary literature hampered metaanalysis [123].…”
Section: Core Element 5: Other Actions Aiming At Responsible Antimicr...mentioning
confidence: 99%
“…The results of our cohort add to available literature by further supporting TM use to provide specialty care to underserved patient populations. Although a bulk of current data reports patient satisfaction around TM, we were able to demonstrate similar clinical outcomes for a complex clinical scenario independent of the mode of ID consultation [ 16 , 24 , 25 ]. In addition to clinical outcomes, we identified that adherence to the SAB bundle was not different by mode of care delivery.…”
Section: Discussionmentioning
confidence: 77%